Personality disorders and cigarette smoking in adult population: a systematic review - Yousef, Hind; Cano-García, Francisco Javier; López-Núñez, Carla (Current psychology (New Brunswick, N.J.), 2024)
Cigarette smoking has long been associated with mental health problems, yet the specific links between smoking behavior, pathological personality traits (as defined by the Big-Five), and personality disorders (PDs) remain insufficiently explored, especially in adult populations. This systematic review seeks to fill this gap by examining the relationship between smoking, personality traits, and PDs, contributing to a better understanding of the psychological factors influencing smoking behavior. Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, our protocol was registered in PROSPERO (CRD42023385420). We conducted a comprehensive search across five electronic databases. After screening with Rayyan software, 17 studies met the inclusion criteria and were incorporated into this review. The findings demonstrated that smokers are more likely to exhibit higher levels of extraversion, openness to experience, and neuroticism, while showing lower levels of conscientiousness. Moreover, smoking behavior was found to have significant correlations with several PDs, including higher associations with schizotypal, borderline, and antisocial PDs, and lower associations with avoidant PD. This study contributes to the field by providing important insights into the connection between smoking behavior, pathological personality traits, and PDs. It addresses a critical gap in the literature, offering evidence that individual personality profiles play a key role in smoking behavior. These findings underscore the need for personalized smoking cessation programs that account for personality-based risks, particularly for individuals with heightened vulnerability due to certain PDs.